2008
DOI: 10.1073/pnas.0711730105
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform distribution of glucosinolates in Arabidopsis thaliana leaves has important consequences for plant defense

Abstract: The spatial distribution of plant defenses within a leaf may be critical in explaining patterns of herbivory. The generalist lepidopteran larvae, Helicoverpa armigera (the cotton bollworm), avoided the midvein and periphery of Arabidopsis thaliana rosette leaves and fed almost exclusively on the inner lamina. This feeding pattern was attributed to glucosinolates because it was not evident in a myrosinase mutant that lacks the ability to activate glucosinolate defenses by hydrolysis. To measure the spatial dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
242
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(257 citation statements)
references
References 40 publications
(33 reference statements)
14
242
1
Order By: Relevance
“…PAPST1 expression corresponds to the sites of biosynthesis and accumulation of known sulfated compounds, for example, GS, and generally overlaps with the expression of several genes of GS biosynthesis and regulation, particularly of APK1 (Mikkelsen et al, 2004;Schuster et al, 2006;Gigolashvili et al, 2007aGigolashvili et al, , 2009bMalitsky et al, 2008). GS are known to be abundant in tissues surrounding the main and peripheral veins (Shroff et al, 2008); correspondingly, high PAPST1 promoter activity was detectable in the vasculature ( Figure 5) as is the case for genes encoding PSK precursors (Kutschmar et al, 2009;Stührwohldt et al, 2011). However, PAPST1 is also localized to developing seeds, which do not produce GS and in which APK expression is limited to the funiculus or radicle .…”
Section: Discussionmentioning
confidence: 99%
“…PAPST1 expression corresponds to the sites of biosynthesis and accumulation of known sulfated compounds, for example, GS, and generally overlaps with the expression of several genes of GS biosynthesis and regulation, particularly of APK1 (Mikkelsen et al, 2004;Schuster et al, 2006;Gigolashvili et al, 2007aGigolashvili et al, , 2009bMalitsky et al, 2008). GS are known to be abundant in tissues surrounding the main and peripheral veins (Shroff et al, 2008); correspondingly, high PAPST1 promoter activity was detectable in the vasculature ( Figure 5) as is the case for genes encoding PSK precursors (Kutschmar et al, 2009;Stührwohldt et al, 2011). However, PAPST1 is also localized to developing seeds, which do not produce GS and in which APK expression is limited to the funiculus or radicle .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Shroff et al (2008) observed that Helicoverpa armigera larvae showed a non-uniform feeding pattern in leaves of A. thaliana, avoiding the midvein and the edge of the leaf, which are glucosinolate-enriched parts. These results suggested that the high amount of glucosinolates on the leaf periphery may act repulsing the insects that start feeding from the edge of the leaf (Shroff et al 2008).…”
Section: Defense Against Biotic Stressmentioning
confidence: 99%
“…Beekwilder et al (2008) found that weight gain was 2.6-fold higher for larvae fed on double-mutant Arabidopsis (myb28 myb29) completely lacking aliphatic glucosinolates and 1.8-fold higher for larvae fed on single-mutant Arabidopsis with intermediate levels of aliphatic glucosinolates compared to WT plants (Beekwilder et al, 2008). Our results are consistent with the report by Shroff et al (2008) that H. armigera larvae avoid the glucosinolate-rich mid-vein and leaf periphery when feeding on Arabidopsis leaves.…”
Section: Effect Of Endogenous Glucosinolates On H Armigera Survivalsupporting
confidence: 83%
“…Glucosinolates are plant secondary metabolites, found in members of the Brassicaceae family, which have insecticidal effects on insect pests such as H. armigera (Hopkins et al, 2009;Muller et al, 2010;Bohinc et al, 2012;Kos et al, 2012;Mithofer and Boland, 2012). Herbivory of Arabidopsis by H. armigera has been shown in induce production of indolic glucosinolates (BadenesPerez et al, 2013) and H. armigera were shown to avoid feeding on the mid-vein and periphery of Arabidopsis rosette leaves where the concentration of the major glucosinolates is highest (Shroff et al, 2008). (C) Photograph of larvae after feeding on WT and gluc-null Arabidopsis for 9 days.…”
Section: Resistance Of Transgenicmentioning
confidence: 99%